History, Cultural Shifts, and Adaptation in Social Change: An Ethnographic Study in the Aboge Islamic Community - Arif Saefudin; Ayu Citra Santyaningtyas; Arief Fahmi Lubis; Sabil Mokodenseho (Yayasan Keluarga Guru Mandiri, 2023)
The Aboge Islamic community faces significant challenges in facing global changes in an increasingly dynamic lifestyle. This research aims to identify the history and primary teachings of Aboge Islam that are adhered to, analyze changes or shifts in values that occur in the Aboge Islamic community, and find adaptation strategies in preserving the values of the teachings during social change. The method used was qualitative, with an ethnographic approach as a research method. Ethnographic research was used to study the culture and society of the Aboge Islamic community. The results show that the Aboge Islamic community experienced changes in its belief system and rituals due to development, education, urbanization, and da'wah. This community adopts a specialized adaptation strategy consisting of conservative and resistance approaches to maintain their traditional religious and cultural practices. With great passion and determination, they maintain the values of their ancestral cultural heritage, demonstrating that their existence and religious practices are still relevant in today's modern era. This research is very important because it can contribute to helping the government in taking the right policy for the preservation of local religious values in other areas.